Prevention and treatment of wound complications at alloplasty of the complex abdominal wall defects - Lysenko, R. B. (Zaporozhye Medical Journal, 2016)
One of the major reasons causing the unsatisfactory results of the alloplasty of complex abdominal wall defects (CAWD) is the development of wound complications (WC), the frequency of which varies from 7.9 to 49.2%. The aim of the research was to identify measures for prevention and treatment of wound complications in alloplasty of the complex abdominal wall defects. Materials and methods. 360 operated patients with CAWD were recruited in the period from 2005 to 2015 in the surgical clinic of the 1-st Poltava hospital. 309 (85.8%) of them were women, 51 (14.2%) - men. Average age was 61 years. Planned operations were in 294 (81.7%) patients, emergency – 47 (13.0%), delayed operations were in 19 (5.3%) patients. Results. In patients with CAWD considerable attention to WC prevention was separately assessed on several stages: before, during and after surgery. Proposed techniques developed by us allows to achieve not only a reliable closure of the defect abdominal wall, but also to reduce the number of regional administration in patients with CAWD with increased risk of development: seroma was diagnosed in 9 (2.5%) patients, hematoma – 2 (0.6%), subcutaneous serous infiltration – 5 (1.4%), purulent wound infection – in 2 (0.7%), the formation of «meshoma» – in 1 (0.3%), abdominal wall abscess – in 1 (0, 3%), ligature fistula – in 3 (0.8%). Relapse was diagnosed in 6 (1.7%) patients. Average hospital stay was 10,2±3,4 days. Conclusions. Using the proposed preventive and therapeutic principles at all stages of the treatment of patients with CAWD individual approach can reduce the number of postoperative WC to 6.4%, significantly improve the results of surgical treatment of these patients.